Efficacy of recombinant factor VIIa for severe bleeding complicated by platelet transfusion refractoriness in patients with hematologic malignancies. Issue 160 (December 2017) - Chu, Tiantian; Tang, Yaqiong; Wang, Hong; Qi, Jiaqian; Zhao, Ying; Pan, Tingting; Tang, Xiaowen; Qiu, Huiying; Fu, Chengcheng; Ruan, Changgeng; Wu, De-Pei; Han, Yue
Abstract: Introduction: Severe bleeding with platelet transfusion refractoriness (PTR) is a common complication associated with reduced survival in patients with hematologic malignancies. The present study aimed to evaluate the efficacy of recombinant factor VIIa (rFVIIa) for severe bleeding complicated by PTR. Materials and methods: Sixty-four patients suffering from severe bleeding with PTR hospitalized in our center between September 2012 and December 2016 were enrolled in this study. Thirty-two patients received rFVIIa (rFVIIa group) and other conventional hemostatic treatments, while the other 32 patients received conventional hemostatic treatments other than rFVIIa (control group). Results: The baseline parameters of patients before treatment were similar in both groups. The total response rates to hemostatic treatment at 24 h and 48 h were significantly higher in the rFVIIa group compared with the control group (p = 0.014, p = 0.020, respectively). Significantly more patients in the rFVIIa group achieved complete responses (CR) at 24 h (p = 0.031), 48 h (p = 0.039), and 72 h (p = 0.021) compared with the control group. The bleeding score (p = 0.029), time to control bleeding (p = 0.034), and activated partial thromboplastin time (p = 0.021) after hemostatic treatment were significantly lower in the rFVIIa group compared with the control group. Patients who achieved a CR to rFVIIa had a significant survival advantage compared with those with a partial response/no response (p = 0.020). No complications with venous or arterial thromboembolism were observed during treatment. Conclusions: rFVIIa may provide effective and safe hemostasis in patients suffering from severe bleeding and PTR. Highlights: rFVIIa could effectively control severe bleeding complicating with PTR in patients with hematologic malignancies. Patients who achieved a CR to rFVIIa had a significant survival advantage compared with those with a PR/NR. The dose of rFVIIa used in this study did not increase thrombotic complications.